Organization of the Educational Process for Qualified Teaching of the Course “Technology of Mechanical Engineering” - M., Mamadjanov A.; Z., Atadjanova M. (International Journal on Integrated Education, 2023)
This article contains the main directions for organizing the educational process. Moreover, the types of organizations that are more efficient and innovative that can interest and instill knowledge in students of technical universities is considered.